2022
DOI: 10.1111/exsy.13093
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence of medical things for disease detection using ensemble deep learning and attention mechanism

Abstract: In this paper, we present a novel paradigm for disease detection. We build an artificial intelligence based system where various biomedical data are retrieved from distributed and homogeneous sensors. We use different deep learning architectures (VGG16, RESNET, and DenseNet) with ensemble learning and attention mechanisms to study the interactions between different biomedical data to detect and diagnose diseases. We conduct extensive testing on biomedical data. The results show the benefits of using deep learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The deep neural network contains several layers of nodes, and these are like neurons which are grouped into layers. [ 57,58 ] Accuracy is one of the important metric that is used to quantify the measurement of correct predictions/classifications. It can be calculated by the following equation Accuracy=Number0.16em0.16emof0.16em0.16emcorrect0.16em0.16empredictionsTotal0.16em0.16emnumber0.16em0.16emof0.16em0.16empredictionsnewline=TP+TNTP+TN+FP+FN$$\begin{eqnarray} {\rm{Accuracy}} &=& {{{\rm{Number}}\,\,{\rm{of}}\,\,{\rm{correct}}\,\,{\rm{predictions}}} \over {{\rm{Total}}\,\,{\rm{number}}\,\,{\rm{of}}\,\,{\rm{predictions}}}}\nonumber\\ &=& {{\sum {\rm{TP}} + {\rm{TN}}} \over {\sum {\rm{TP}} + {\rm{TN}} + {\rm{FP}} + {\rm{FN}}}}\end{eqnarray}$$…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep neural network contains several layers of nodes, and these are like neurons which are grouped into layers. [ 57,58 ] Accuracy is one of the important metric that is used to quantify the measurement of correct predictions/classifications. It can be calculated by the following equation Accuracy=Number0.16em0.16emof0.16em0.16emcorrect0.16em0.16empredictionsTotal0.16em0.16emnumber0.16em0.16emof0.16em0.16empredictionsnewline=TP+TNTP+TN+FP+FN$$\begin{eqnarray} {\rm{Accuracy}} &=& {{{\rm{Number}}\,\,{\rm{of}}\,\,{\rm{correct}}\,\,{\rm{predictions}}} \over {{\rm{Total}}\,\,{\rm{number}}\,\,{\rm{of}}\,\,{\rm{predictions}}}}\nonumber\\ &=& {{\sum {\rm{TP}} + {\rm{TN}}} \over {\sum {\rm{TP}} + {\rm{TN}} + {\rm{FP}} + {\rm{FN}}}}\end{eqnarray}$$…”
Section: Resultsmentioning
confidence: 99%
“…The deep neural network contains several layers of nodes, and these are like neurons which are grouped into layers. [57,58] Accuracy is one of the important metric that is used to quantify the measurement of correct predictions/classifications. The classification using the deep neural network with artificial neurons provides an efficiency of ≈94% (Figure 7c).…”
Section: Dnn/ml Results For the Classification/prediction Of Differen...mentioning
confidence: 99%
“…Ahmed et al developed seven ensemble models combining different ML algorithms, including naïve Bayes, decision tree, random tree, random forest, support vector classifier, logistic regression, adaptive boosting, gradient boosting, support vector machine with sequential minimal optimization, and JRip, to detect Android ransomware and to mitigate adversarial evasion attacks and found that the ensemble methods performed better than the individual ML algorithms [ 53 ]. Djenouri et al used several deep learning architectures such as VGG16, RESNET, and DenseNet with an efficient ensemble learning and attention mechanism and achieved a disease detection rate of 92% [ 54 ]. Once we obtain additional data with significantly more subjects, we will investigate hybrid ensemble methods and check whether they perform better than the ML algorithms proposed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to use IoT devices to distantly capture and relay this information to significant health data collection and diagnostic centers (e.g., cardiovascular, blood pressure, and anatomy data) (Luong et al (2016), Sharma, Al‐Wanain, et al (2022)). The most critical risks to healthcare facilities are data protection and privacy of the patient data collected for medical purposes (Djenouri et al (2022), Tariq, Asim, and Al‐Obeidat (2019)).…”
Section: Machine Learning and Internet Of Thingsmentioning
confidence: 99%